2016
DOI: 10.1590/1806-9282.62.05.428
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile and prognostic factors in patients with lung cancer

Abstract: Objective: To describe the epidemiological profile of patients with lung cancer treated at a public tertiary referral hospital specializing in oncology, and to explore variables that may be related to the overall survival (OS) of these patients. Method: Data from the medical records of all patients with invasive lung cancer consecutively seen at the Oncology Department of Hospital Estadual Mário Covas between August 2008 and December 2013 were extracted. The information obtained was submitted to statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…These data are concordant with those of previous studies (8)(9)(10); to the best of our knowledge, this is the first report of associations between pre-treatment hemoglobin levels and the prognosis of patients with NSCLC, independent of whether they had received chemotherapy and/or lobectomy, in Henan, China. Compared with previous studies (8)(9)(10)(11)15), the multivariate models performed in the current study included more factors, rendering the present results less confounded.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These data are concordant with those of previous studies (8)(9)(10); to the best of our knowledge, this is the first report of associations between pre-treatment hemoglobin levels and the prognosis of patients with NSCLC, independent of whether they had received chemotherapy and/or lobectomy, in Henan, China. Compared with previous studies (8)(9)(10)(11)15), the multivariate models performed in the current study included more factors, rendering the present results less confounded.…”
Section: Discussionmentioning
confidence: 76%
“…Hemoglobin is a biochemical biomarker assessed during clinical examination. Several reports have indicated that low hemoglobin levels are associated with poor survival in patients with NSCLC (8)(9)(10); however, contradictory reports also exist (11,12). Whether hemoglobin levels, especially low pre-treatment hemoglobin (LPHb) levels, are an independent predictor for poor prognosis in patients with NSCLC requires further study for clarification.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, because they contributed to the morbidity and mortality rates, they were defined as limiting for this study. 15 It is also considered the underreporting of deaths as another form of research restriction during data collection. Within this context, there is a high proportion of registered mortality rates with ill-defined causes, although MIS is well established in the country.…”
Section: Methods Introductionmentioning
confidence: 99%
“…13 Another challenge is in relation to epidemiological studies on lung cancer, since many of them do not depict the specific histological type of the neoplasm and this represents a change in the lifetime of the individual depending on the type of tissue reached by the malignant tumor. 15 The country's territorial extension contributes significantly to the collection of results. According to IBGE, the distance between the north and south ends of Brazil is 4398 kilometers (latitude range from 05 ° 16 'N to 33 ° 45' S).…”
Section: Methods Introductionmentioning
confidence: 99%
See 1 more Smart Citation